ENHANCING GOOD GOVERNANCE TROUGH PUBLIC SECTOR PERFORMANCE AUDITS: THE MEDIATING ROLE OF FINANCIAL MANAGEMENT ACCOUNTABILITYk - Putri Nabila; Isra Maulina (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2025)
The increasing demand for transparent and accountable public governance has highlighted the strategic role of performance audits in strengthening public financial management. While previous studies have extensively discussed either performance auditing or financial accountability, limited attention has been given to how financial management accountability functions as a mechanism through which performance audits contribute to the realization of good governance. This study aims to examine the effectiveness of public sector performance audits in promoting good governance through financial management accountability in Indonesia. A qualitative descriptive approach was employed using documentary research and non-participant observation. The data consisted of government financial statements, performance audit reports issued by the Audit Board of the Republic of Indonesia (BPK), fiscal regulations, government policy documents, and relevant academic literature. Data were analyzed using qualitative content analysis involving data organization, reduction, interpretation, and source triangulation to ensure the credibility of the findings. The results indicate that performance audits significantly strengthen financial management accountability by improving transparency, internal control systems, and outcome-based public financial reporting. The implementation of Government Accounting Standards (SAP) further enhances the quality and reliability of financial reporting, thereby supporting the realization of good governance. Nevertheless, the effectiveness of accountability remains constrained by disparities in human resource capacity, limited digital financial management systems, and organizational resistance to transparency. The study contributes to the public governance literature by emphasizing the mediating role of financial management accountability in linking performance audits with good governance. Practically, the findings highlight the importance of strengthening auditor competencies, digital governance, institutional commitment, and integrated oversight systems to promote sustainable and accountable public sector governance.